Japan : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Japan. (IMF Staff Country Reports; Country Report ;, 2020)
This 2019 Article IV Consultation with Japan highlights that the rapid aging and shrinking of Japan's population has become central to macroeconomic policies and outcomes. The consultation centered on the macroeconomic effects of Japan's demographics. Mutually reinforcing policies are needed to lift current and expected inflation, stabilize public debt, and raise potential growth. Underlying growth is expected to remain resilient but will be increasingly challenged by slowing external demand and intensifying demographic headwinds. Growth in domestic demand is being eroded by the weaker external environment. Frontloading of private consumption ahead of the October 2019 consumption tax rate increase appears to have been smaller than in 2014.